Education, Migration and Development Critical Perspectives in a Moving World - North, Amy; Chase, Elaine (Bloomsbury Academic, 2022)
This open access book looks critically at how education, migration and development intersect and interact to shape people, communities, societies, ideas, values, and action at local, national and international levels. Written by leading scholars and practitioners based in Belgium, China, Columbia, Ethiopia, India, Lebanon, Mongolia, South Africa, the UK and the USA, the book introduces the reader to how such interactions play out through a series of case study examples drawn from across the globe. It explores education in all its forms and raises critical questions about its purpose and value in different low- and middle-income contexts and settings, in the context of migration. The contributors engage with the multiple reasons why people move, and also consider how people and societies are shaped not just by the movement of humans but also of ideas, concepts and values across different national and international contexts. The chapters cover a range of topics and themes including gender and feminisation, dignity, internal migration, migrant camps, museum pedagogies, migrant teachers and migrant identities. The book decentres dominant theories and ideas emerging in global north scholarship and prioritises empirical studies conducted in relation to low- and middle- income country contexts written by scholars from those contexts where possible.